Timeline of Records Management in Indonesian Universities (Case Studies of Faculty of Engineering, University of Indonesia) - Puspitasari Srirahayu, Dyah; Kom, S; Hum, M (International Journal of Engineering and Technology, 2018)
The aim of this research is to understand the development records management in universities, especially in Faculty of Engineering, University of Indonesia (FT UI). Records management is required to ensure the accountability and transparency of an organization. In order to manage it, a specific unit is needed. This research uses qualitative approach with case study method to provide a complete description of how is the development of records management in FT UI overtime. It can be found in the result that from year to year, the records management in FT UI does not have a clear structure even though the occupation is available and goes well. The employees do records management based on their knowledge that they have and inherited from generation to generation.Â Â